OPTIMIZATION OF SPORTS LEARNING THROUGH A LITERACY APPROACH - Chairad, Muhammad (Journal of Physical Education, Health and Sports Recreation, 2023)
This research aims to conduct a literature review to document and analyze the latest developments in optimizing sports learning through a literacy approach. This study focuses on understanding the concept of literacy in the context of sports, its impact on learning outcomes, as well as challenges and implementation strategies. This article discusses an innovative approach in optimizing sports learning through a literacy approach. This approach not only emphasizes the physical aspects and skills of athletics, but also involves a deep understanding of the language and literacy contexts associated with sport. Through a literature review, this article explores the basic concepts of literacy in a sports context, highlighting the benefits of integrating literacy in sports learning. Empirical findings are presented to show the positive impact of using a literacy approach on understanding sports concepts, match analysis and team communication. The conclusions from the results of this research provide a comprehensive picture of the importance of a literacy approach in sports learning, making a significant contribution to the development of holistic and quality sports education in the future.